Friedel–Crafts Alkylation of Aromatics by TiCl4-Promoted Ring Cleavage of 3-Arylcyclobutanones - Kanie, Mayu; Yoshimura, Tomoyuki; Matsuo, Jun-ichi (Synthesis, 2018)
Ring cleavage of 3-arylcyclobutanones and successive Friedel–Crafts alkylation of methoxy- or alkyl-substituted benzene derivatives proceeded to give 3,3-diarylbutan-2-ones by activation with titanium tetrachloride.
Keywords: cyclobutanone; Friedel–Crafts alkylation; ring cleavage; Lewis acid; aromatics